Evaluating Local Wisdom-Based Learning Media in Early Childhood Education - Yetty Isna Wahyuniseptiana; Singgih Subiyantoro; Oka Irmade (Universitas Veteran Bangun Nusantara, 2026)
Instilling local wisdom values in early childhood is crucial for strengthening cultural identity and contextual learning. Learning media based on local wisdom needs to be developed and its effectiveness evaluated in early childhood education. This study aims to evaluate the quality of local wisdom-based instructional media for early childhood education across five aspects: systematics, language, substance, graphics, and usefulness. A descriptive quantitative survey was conducted with 100 early childhood teachers in Surakarta. The instrument was a validated questionnaire using a four-point rating scale. Reliability testing confirmed internal consistency, and ethical protocols (informed consent, anonymity) were observed. The research results show that, Findings reveal that systematics and usefulness scored highest, showing that the media is well-structured and supportive for teaching practice. In contrast, the substance and graphic aspects scored lower, indicating limited content depth and visual quality. Divergent views were noted on the use of foreign terms. Local wisdom-based instructional media is highly relevant and useful, but improvements are required in substance integration and visual design. This study contributes novelty by providing a comprehensive evaluation framework for media grounded in local culture. Practical implications highlight the importance of contextualizing media development for teachers, while future research should examine direct impacts on children’s learning outcomes.